Multi-functional hindered amine light stabilizers-functionalized carbon nanotubes for advanced ultra-high molecular weight Polyethylene-based nanocomposites. (1st December 2015) - Dintcheva, N.Tz.; Arrigo, R.; Morici, E.; Gambarotti, C.; Carroccio, S.; Cicogna, F.; Filippone, G.
Abstract: Hindered Amine Light Stabilizer (HAS) molecules have been covalently linked on the outer surface of multi-walled carbon nanotubes (CNTs), and the so-obtained multi-functional fillers (HAS- f -CNTs) have been compounded with Ultra High Molecular Weight Polyethylene (UHMWPE) to get composite films. The success of the grafting reaction of the HAS molecules has been confirmed through spectroscopic and thermo-gravimetric analyses. Morphological analyses reveal a segregated microstructure, in which CNT-rich channels surround the polymer domains. This morphology results in improved mechanical properties and appreciable electrical conductive features. More importantly, the addition of only 1 wt.% of HAS- f -CNTs brings about a significant improvement of the photo-oxidation resistance, which neither HAS nor CNTs can provide if used separately. The origin of this synergic effect is discussed. Overall, our results demonstrate the possibility of using properly functionalized CNTs as multi-functional fillers to get high-performance polymer composites.